VD_FINDINFO HC / 2025 / 825 vom 21. November 2025 - VD Tribunal cantonal (2025)
EXPULSION DE LOCATAIRE, CAS CLAIR, BAIL À LOYER, ADMISSION DE LA DEMANDE | 120 al. 1 CO, 120 al. 2 CO, 257d CO, 259g CO, 257 al. 1 CPC (CH)